(untitled) (The Geographic Base, 2024)
Landslides triggered by heavy rainfall pose a significant threat to communities and the infrastructure in the hilly region. Most of the landslides occur during the monsoon season. Since the risks associated with rainfall-induced landslides are unknown, in the study area a detailed examination of these risks is necessary for sustainable planning and disaster risk management. This study relied on a Geographic Information System (GIS) to integrate SRTM data with additional datasets to estimate and map landslide susceptibility in Budhiganga Municipality and Chhededaha Rural Municipality. six parameters- slope, LULC, geology, rainfall, drainage density, and elevation were analyzed using three Digital Elevation Model (DEM), Climatic Research Unit (CRU), hydrostatics SRTM data, geology data, and landslide data. A landslide susceptibility map was generated by categorizing the terrain into five major groups: very low, low, moderate, high, and very high. Then the obtained results were compared with existing landslide maps, providing valuable insights for planning and development, while also identifying areas with a higher likelihood of future landslides, ultimately reducing the risk of potential damage in the Budhigana Municipality and Chhededaha Rural Municipality.